Magnetic windows cleaner / Muhammad Saiful Ridzuan Mazlan ... [et al.] - Mazlan, Muhammad Saiful Rizuan; Abd Bari, Ahmad Alawi; Mohamad Nasri, Nasrin Dayana; Mohamad Zaki, Zarith Nurfarisa (2017)
There is disclosed a variable strength magnetic window cleaning product having a outer and inner unit utilizing magnetic force to simultaneously clean both the inside and outside panes of window. When a user moves the inner unit from inside, the outer unit follows the inner unit along the window, thus cleaning both sides of the window panes simultaneously. A replaceable cleaning surface such as fiber cloth or disposable wipe is secured across the engagement surface area and contacts the window surface to effect the cleaning.